2019
DOI: 10.1002/ejic.201900630
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Iodides – from Obscurity to Bright Luminescence

Abstract: This review is dedicated to the chemistry of Mo iodides. These compounds have a humble origin, and for a long time their chemistry has been almost completely neglected. Although important work on mononuclear and dinuclear Mo iodide complexes was done in 1980-1990s, the situation has dramatically changed within the last decade. The finding that the IntroductionThe iodides of transition metals attract much less attention than their chloride and bromide analogues, even though a book dealing exclusively with metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 134 publications
(263 reference statements)
2
46
0
Order By: Relevance
“…In general, all emission spectra for the tungsten clusters prolonged to the blue region for ≈ 50 nm, which leads to a more orange color of emission in comparison with the molybdenum ones , , . Interestingly, the emission profiles of iodide tungsten clusters, as well as of molybdenum ones, are independent of apical ligands indicating strong core‐centered nature of luminescence, which correlates well with the literature , , . On the other hand, the excitation spectra of all investigated compounds in solutions, including (Bu 4 N) 2 [{Mo 6 I 8 }(OTs) 6 ], are almost identical, with a maximum at ≈ 350 nm (Figure , Figure S5).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…In general, all emission spectra for the tungsten clusters prolonged to the blue region for ≈ 50 nm, which leads to a more orange color of emission in comparison with the molybdenum ones , , . Interestingly, the emission profiles of iodide tungsten clusters, as well as of molybdenum ones, are independent of apical ligands indicating strong core‐centered nature of luminescence, which correlates well with the literature , , . On the other hand, the excitation spectra of all investigated compounds in solutions, including (Bu 4 N) 2 [{Mo 6 I 8 }(OTs) 6 ], are almost identical, with a maximum at ≈ 350 nm (Figure , Figure S5).…”
Section: Resultssupporting
confidence: 83%
“…The substitution of apical iodide ligands leads to a small hypsochromic shift of absorption and to significant changes in the spectrum shape. This effect, although a more pronounced one, has been repeatedly demonstrated for molybdenum complexes and is probably associated with a significant contribution of apical ligands to the HOMO , , , , , . In general, from the obtained spectra it can be concluded that (i) the initial complex (Bu 4 N) 2 [{W 6 I 8 }I 6 ] has higher absorption in the visible region and (ii) the isothiocyanate and azide complexes have similar absorption profiles, but the extinction coefficient of 2 is slightly lower.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations